Pengaruh Motivasi dan Komunikasi Terhadap Kinerja Karyawan di Kuta Central Park Hotel Kuta Bali - Yuda, Ida Bagus Nyoman Krisna Prawira; Antari, Ni Luh Sili (Jurnal Mosaik Hospitaliti, 2022)
This study aims to determine the effect of Motivation (X1) and Communication (X2) on Employee Performance (Y) at Kuta Central Park Hotel. Respondents used in this study were all Kuta Central Park Hotel employees with a total of 73 respondents. The primary data used in this study was derived from questionnaires. The questionnaire is tested using validity and reliability tests followed by classical assumption tests and the hypothesis is proven using multiple linear regression analysis. The results of this study indicate that 1) Motivation (X1) has a positive and significant influence on Employee Performance (Y); 2) Communication (X2) has a positive and significant influence on Employee Performance (Y); 3) Motivation (X1) and Communication (X2) have an effect of 74.1% on Employee Performance (Y) at Kuta Central Park Hotel. While the remaining 25.9% is influenced by other variables not examined in this study, and 4) Communication (X2) is an independent variable that has a dominant effect on Employee Performance (Y) at Kuta Central Park Hotel. The findings of this study indicate that hotel management should pay more attention to motivation and communication to improve employee performance.